Pengaruh Lingkungan Sekolah terhadap Keterampilan Berbicara Siswa: The Influence of School Environment on Students' Speaking Skills - Jusniati Jusniati; Jumiati Jumiati; Nuraini Kasman; Aswadi Aswadi (Information Technology and Science(ITScience), 2026)
This study aims to determine the influence of the school environment on students' speaking skills at SMP Negeri Satap 12 Batu, Leppangeng Village, Sidenreng Rappang Regency. The background of this study is that students' speaking skills still pose problems, including a lack of fluency in expressing opinions, low self-confidence, and language use that is not fully in accordance with Indonesian language rules. These conditions are thought to be related to the school environment, which includes the learning atmosphere, social interactions, and learning facilities. This study uses a quantitative approach with a correlational-causal research design. The study population and sample consisted of 43 students, using a total sampling technique. Data collection was carried out through questionnaires, observations, interviews, and documentation. The data obtained were analyzed using the Pearson product-moment correlation test and simple linear regression. The results of the study indicate a positive and significant relationship between the school environment and students' speaking skills, with a correlation value of 0.395 and a significance of 0.009 (<0.05). The results of the regression test indicate that the school environment accounts for 15.6% of students' speaking skills, while factors outside the study influence 84.4%. Based on these results, it can be concluded that the school environment has a low-to-moderate influence on students' speaking skills. Therefore, efforts are needed to create a more conducive school environment to enable students' speaking skills to develop optimally.